Coincidence and Common Fixed Point results in G-metric Spaces using Generalized Cyclic Contraction: Sejal V. Puvar, Rajendra G. Vyas - Team, Support (Thai Journal of Mathematics, 2022)
Here, we have established the generalized cyclic contractive condition in G-metric spaces which can’t be reduced to the contractive condition in standard metric spaces. The coincidence and common fixed point results are obtained for the pair of (A,B)-weakly increasing mappings in G-metric spaces.